2009
DOI: 10.1007/s10549-008-0262-4
|View full text |Cite
|
Sign up to set email alerts
|

Fok1 polymorphism of vitamin D receptor gene contributes to breast cancer susceptibility: a meta-analysis

Abstract: Several polymorphisms in the vitamin D receptor (VDR) gene have been reported to influence breast cancer risk. However, the published findings have been conflicting. We conducted a meta-analysis of 21 case-control studies with Fok1 (eight studies with 5,284 cases and 7,500 controls), Bsm1 (14 studies with 5,498 cases and 7,943 controls), Apa1 (four studies with 1,138 cases and 7,943 controls), Taq1 (10 studies with 4,459 cases and 5,485 controls) polymorphisms. The results showed Fok1 polymorphism was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
64
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 33 publications
12
64
2
2
Order By: Relevance
“…It produces a variety of biologic effects by interacting with specific nucleotide sequences of target genes. The VDR is known to be a crucial mediator of the cellular effects of vitamin D and interacting with cell signaling pathways to influence cancer development (Kearney et al 1996;Deeb et al 2007;Ishihara et al 2008;Theodoratou et al 2008;Tang et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It produces a variety of biologic effects by interacting with specific nucleotide sequences of target genes. The VDR is known to be a crucial mediator of the cellular effects of vitamin D and interacting with cell signaling pathways to influence cancer development (Kearney et al 1996;Deeb et al 2007;Ishihara et al 2008;Theodoratou et al 2008;Tang et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The FokI polymorphism is located near the 5′-UTR region of the gene within the DNA-binding domain (Kanan et al 2000;Ingles et al 2001;Kim et al 2001;Chen et al 2002;Tworoger et al 2009). Studies have explored the associations between VDR polymorphisms and human cancers, including colorectal adenomas, prostate cancer, breast cancer, bladder cancer and melanoma (Kearney et al 1996;Deeb et al 2007;Slattery 2007;Ishihara et al 2008;Theodoratou et al 2008;Tang et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these differences might also result from confounding factors that are taken into consideration in these studies and include food habits, age, education, menopausal status, parity, body-mass index, use of oral contraceptives or hormone replacement therapy, tubal ligation, and others (Lurie et al, 2007(Lurie et al, , 2011Tworoger et al, 2009). The BsmI or FokI SNPs in VDR have been associated with breast, bladder, renal, carcinoma, and cutaneous malignant melanoma and nonmelanoma skin cancer (Mittal et al, 2007;Gandini et al, 2009;Tang et al, 2009;Arjumand et al, 2012). These polymorphisms were also recognized as risk factors of hepatocellular, head and neck, thyroid, prostate, and colorectal cancers (Liu et al, 2005;Mishra et al, 2005;Bai et al, 2009Bai et al, , 2012Penna-Martinez et al, 2009;Falleti et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are still a lot of debates on the relationship between VDR polymorphism and the risk of breast cancer development. Case-control studies on Fok1 in breast cancer showed some evidence of increased risk among ff carriers (Sinotte et al, 2008;Gapska et al, 2009;McKay et al, 2009), which was confirmed by some later metaanalysis Tang et al, 2009;. However, these studies also reported some decreased risk among ff carriers (Anderson et al, 2011), or no association with breast cancer (Curran et al, 1999;Guy et al, 2004;John et al, 2007;Abbas et al, 2008;Engel et al, 2012;Rollison et al, 2012;Fuhrman et al, 2013;Mishra et al, 2013;Shahbazi et al, 2013).…”
Section: Introductionmentioning
confidence: 88%
“…It participates in a wide variety of biological process including bone metabolism, immune response modulation, and regulation of cell proliferation and differentiation in its active form of vitamin D (1,25(OH)D3), and all these collectively play an important role in the carcinogenesis of cancer . Previous studies have demonstrated that VDR expression was decreased in breast cancer cell (Lopes et al, 2010), and the expression and/or function of the VDR protein is influenced by the polymorphism in the VDR gene (Tang et al, 2009).…”
Section: Introductionmentioning
confidence: 98%